Outcome of CC7 transfer to median nerve and deep branch of ulnar nerve for patients with global brachial plexus avulsion - Liu, Yuzhou; Yu, Hu; Liu, Jingbo; Lao, Jie (Frontiers in Medicine, 2025)
IntroductionAs for global brachial plexus avulsion, the recoveries of intrinsic muscles are not satisfying after nerve transfers.MethodsA retrospective review of 31 patients treated with different CC7 transfers after GBPA was carried out. The modified group: CC7 transfer to median nerve and DBUN by medial antebrachial cutaneous nerve (MACN). The conventional group: CC7 transfer to median nerve. The mean follow-up period was 3 years.ResultsAfter CC7 transfers, one patient got M3, one patient got M2 and two patients got M1 in abductor digiti minimi (ADM) in the modified group, while no patients had recovery in ADM in the conventional group. The recoveries of abductor pollicis brevis (APB) were similar between two groups. Motor unit potentials (MUP) of ADM and dorsal interosseous muscle (DIM) appeared in 4 and 2 patients respectively after surgery in the modified group. Nobody gained MUP of ADM or DIM in the conventional group. There were no statistical differences of MUP in APB, compound motor action potential (CMAP) in FDPI and FCR between two groups.DiscussionCC7 transfer to median nerve and DBUN by pedicled ulnar nerve and MACN could initially make intrinsic muscles regeneration in patients with GBPA, while not affect the recovery of median nerve.